The Swiss Transplant Cohort Study's Framework for Assessing Lifelong Psychosocial Factors in Solid-Organ Transplants. (September 2013) - De Geest, Sabina; Burkhalter, Hanna; Berben, Lut; Bogert, Laura Jane; Denhaerynck, Kris; Glass, Tracy R.; Goetzmann, Lutz; Kirsch, Monika; Kiss, Alexander; Koller, Michael T.; Piot-Ziegler, Chantal; Schmidt-Trucksäss, Arno; et al.
Background: Understanding outcomes after transplant requires a biopsychosocial model that includes biomedical and psychosocial factors. The latter, to date, are assessed only in a limited way as part of transplant registries or cohort studies. The Swiss Transplant Cohort Study (STCS) is a nationwide open cohort study (starting May 2008) to systematically and prospectively assess psychosocial factors. This article describes the framework underpinning STCS's psychosocial assessment. Methods: The STCS framework was adapted from the multidimensional conceptual perspective of Dew et al to describe transplant psychosocial domains and specific outcomes by adding a time perspective, a system perspective, and interaction among domains. Results: We propose a multidimensional, multilevel biopsychosocial framework representing mutually influencing domains from before to after transplant, and exemplify each domain by factors included in STCS and their measurement. The transplant patient, centrally positioned, is described by clinical and sociodemographic characteristics (eg, socioeconomic status, educational, professional, and relationship status). The following psychosocial domains further describe the patient: (1) physical/functional (eg, perceived health status, sleep quality, daytime sleepiness), (2) psychological (eg, depression, stress), (3) behavioral (eg, medication adherence, smoking, drug use, physical activity, sun protection), (4) social (eg, work capacity/return to work), and (5) global quality of life. Factors associated with health care system level (eg, trust in transplant team) are also included in the model. Conclusion: The STCS's psychosocial framework provides a basis for studying the interplay of biomedical, sociodemographic, psychosocial, behavioral, and health care system factors in view of transplant outcomes and therefore has the potential to guide biopsychosocial transplant research.